2023
DOI: 10.1093/sleep/zsad039
|View full text |Cite
|
Sign up to set email alerts
|

Microglial voltage-dependent anion channel 1 signaling modulates sleep deprivation-induced transition to chronic postsurgical pain

Abstract: Study Objectives This study verified that sleep deprivation before and after skin/muscle incision and retraction (SMIR) surgery increased the risk of chronic pain and investigated the underlying roles of microglial VDAC1 signaling. Methods Adult mice received six hours of total sleep deprivation from one day prior to SMIR until the third days after surgery. Mechanical and heat-evoked pain was assessed before and within 21 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Commencing with entry into the daytime cycle, mice were subjected to 6 h of complete sleep deprivation using a sleep deprivation apparatus in biofeedback mode (XR108S, Shanghai XinRuan Information Technology Co., Ltd.) 20 . The sleep deprivation efficiency of this apparatus has been previously validated 30 . During this process, mice moved naturally and had free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Commencing with entry into the daytime cycle, mice were subjected to 6 h of complete sleep deprivation using a sleep deprivation apparatus in biofeedback mode (XR108S, Shanghai XinRuan Information Technology Co., Ltd.) 20 . The sleep deprivation efficiency of this apparatus has been previously validated 30 . During this process, mice moved naturally and had free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“… 20 The sleep deprivation efficiency of this apparatus has been previously validated. 30 During this process, mice moved naturally and had free access to food and water. The apparatus monitored the animal behaviors and activities, and when mice closed their eyes or stopped moving, the percussion bar started to rotate to disturb them and force them to stay awake.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different kinds of sleep disorders often lead to varied clinical complications and outcomes due to distinct internal pathophysiological mechanisms. It has been demonstrated that reduced sleep time could activate the microglial cells through microglial voltage-dependent anion channel 1 and increase the activity of L-type calcium channels, leading to increased post-operative pain ( 19 , 20 ). Obstructive sleep apnea syndrome is deeply associated with post-operative cognitive dysfunction, and the mechanisms involved include neuroinflammation, impairment of hippocampal synaptic plasticity, and blood–brain barrier dysfunction ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%